Evaluating the impact of tax rebates and exemptions on the financial well-being of pensioners - Kurt Sant (Central Bank of Malta, 2024)
This study evaluates the impact of two pension-related policies introduced in Malta: the 2017 Tax Rebate on Pensions and the 2022 Exempt Pension Income measures. Using EUROMOD microsimulation model, the effects on pensioners' disposable income, work incentives, and financial well-being are simulated for 2017-2027. The findings show that both policies are well-targeted, benefiting pensioners while limiting leakage to other groups. Over 73% of pensioner households - around 40,000 households-saw income gains, with mean equivalised disposable income rising by exteuro328 in 2022 (2.0% of total income), projected to reach exteuro560 by 2027 (3.2% of total income). The average tax burden is expected to drop by 2.6 percentage points by 2027, encouraging delayed retirement. By the later years, the 2022 policy becomes dominant, as expanded exemptions render the 2017 rebates less relevant. While the 2017 policy still aids certain groups, its impact is limited. Although the at-risk-of-poverty rate for pensioners improved, the effects on lower-income groups and income inequality remain modest. The policies' fiscal costs are contained, ensuring sustainability. Overall, future reforms are needed to complement these successful policies and to ensure a resilient pension system in the face of future socio-economic challenges.
Keywords: H24; H55; J26; 330; Pensions; Social Security; Pension Income; Tax Rebates; Tax Exemptions